Granulated refractory fillers for foundry production - V. V. Skurikhin; V. P. Migal; A. N. Novikov (Литьë и металлургия, 2000)
By the specific chemical and phase compositions as well as the shape of grains close to spherical the refractory fillers can find application in foundry production as manufactured fillers.